A Comparative Study on Anemia, Gestational Diabetes and Gestational Hypertension during pregnancy in Rural, Semi Urban and Urban Hospitals in Bangladesh (East West Medical College Journal, 2024)
Most of the women in developing countries undergo health problems in full or part of the pregnancy period. Major complications of pregnancy are anemia, gestational hypertension, and Gestational Diabetes. The objective of this study was to compare the prevalence of anemia, gestational hypertension, and Gestational Diabetes among antenatal women in rural, semi-urban, and urban hospitals. The study was conducted among 384 pregnant mothers who attended for ANC in OPD of Gonosashasthaya Samaj Vittik Medical College Hospital (Savar) , Gonosasthaya Nogor Hospital, (Dhanmondi), Sub-center of Gonosasthaya Kendro (Shimulia, Panisail, Barobaria, Delduwar, Shripur ) from December 2021 to November 2022 by consecutive sampling. The age range of the patients was 18 to 40 years. Mean age was 24.74 years. In this study majority of population 169 (44%) were in age group 18 - 22 years. Most of the pregnant women 291(76%) were housewives, lived in Nuclear families 253(66%) and the maximum population were from lower middle 134 (35%) socio-economic condition. A significant number of pregnant mother ,98(26%) were anemic, 38(10%) had GDM and only 34(9%) were gestational hypertension. Anemia is comparatively more in rural and semi-urban than urban. GDM and gestational hypertension is more in urban areas than rural and semi urban followed by 14(11%) and 20(16%) respectively. Special attention of policy makers, health professional, public health researchers, and the community is required on this regards. So early diagnosis and treatment is required to avoid long-term health problems of the mother and her offspring.EWMCJ Vol. 12, No. 1&2, January-July 2024: 9-13